2008
DOI: 10.1099/ijs.0.65271-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenophaga bisanensis sp. nov., isolated from wastewater of a textile dye works

Abstract: A Gram-negative, non-spore-forming, rod-shaped, Hydrogenophaga-like bacterial strain, K102T , was isolated from wastewater collected from a textile dye works in Korea and subjected to a polyphasic taxonomic study. Strain K102 T grew optimally at pH 7.0-8.0 and 30-37 6C in the presence of 0.5 % (w/v) NaCl. It contained Q-8 as the predominant ubiquinone and C 16 : 0 , C 16 : 1 v7c and/or iso-C 15 : 0 2-OH and C 18 : 1 v7c as the major fatty acids. The DNA G+C content was 64.8 mol%. A neighbour-joining phylogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Subsequently, five other species, Hydrogenophaga intermedia (Contzen et al, 2000), H. atypical, H. defluvii (Kämpfer et al, 2005), H. caeni (Chung et al, 2007) and H. bisanensis (Yoon et al, 2008) have been described. Phylogenetic analysis based on 16S rRNA gene sequences showed that the genus Hydrogenophaga falls within the family Comamonadaceae, class Betaproteobacteria (Anzai et al, 2000;Kämpfer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, five other species, Hydrogenophaga intermedia (Contzen et al, 2000), H. atypical, H. defluvii (Kämpfer et al, 2005), H. caeni (Chung et al, 2007) and H. bisanensis (Yoon et al, 2008) have been described. Phylogenetic analysis based on 16S rRNA gene sequences showed that the genus Hydrogenophaga falls within the family Comamonadaceae, class Betaproteobacteria (Anzai et al, 2000;Kämpfer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Hydrogenophaga are chemo-organotrophic or chemolithoautotrophic, use the oxidation of H 2 as an energy source and CO 2 as a carbon source (Willems et al 1989;Kämpfer et al 2005;Chung et al 2007;Yoon et al 2008;Kimura and Okabe 2013). The genus, at the time of writing the manuscript, comprised of nine recognized species (http://www.bacterio.net/hydrogenophaga.html), namely H. flava, H. palleronii, H. pseudoflava, H. taeniospiralis (Willems et al 1989), H. defluvii, H. atypica (Kämpfer et al 2005), H. bisanensis (Yoon et al 2008), H. caeni (Chung et al 2007) and H. intermedia (Contzen et al 2000) and four unrecognized species H. temperata (Kim et al 2010), H. electricum (Kimura and Okabe 2013), H. carboriunda (Reinauer et al 2014) and H. luteola (Du et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At the time of writing, the genus Hydrogenophaga comprises nine validly published members of the genus (Chun et al, 2007): Hydrogenophaga atypica, Hydrogenophaga defl uvii (Kämpfer et al, 2005), Hydrogenophaga fl ava (Willems et al, 1989), Hydrogenophaga intermedia (Contzen et al, 2000), Hydrogenophaga palleronii, Hydrogenophaga pseudofl ava and Hydrogenophaga taeniospiralis (Willems et al, 1989), Hydrogenophaga caeni (Chun et al, 2007), and Hydrogenophaga bisanensis (Yoon et al, 2008). H. fl ava is the type species of the Hydrogenophaga genus.…”
mentioning
confidence: 99%